ANALISIS DESKRIPTIF MAKNA SOSIAL KULTURAL DALAM RORASA BAHASA TERNATE - Nada, Anwar (Universitas Khairun, 2025)
The urgency of the Ternate language rorasa research is the oral tradition of the North Maluku community, especially the city of Ternate. Some of the similarities are the use of pantuns, cum-cum rorasa which are sung and contain advice in their delivery. This shows that there are similarities in several regions based on the form of the text. However, different performances are interesting and important phenomena to study because they are related to meanings that refer to the local wisdom of the Ternate region, an oral tradition in the form of storytelling art that is passed down from generation to generation.Rorasa is sung in informal situations. In informal situations, rorasa is sung at events such as weddings, deaths. In this study, researchers focus on language as a source of culture and speaking is a language practice. This study examines the meaning of the rorasa oral tradition in a particular community of the Ternate community which is an oral tradition that is passed down from generation to generation.The purpose of this study is (1) to describe the meaning of the rorasa oral tradition and its implications for anthropolinguistic learning. (2) explain how the implications of oral tradition are on anthropolinguistic learning. The method used in this study is a qualitative descriptive research method. The informants in this study were the people of Ternate city, especially in Tubo sub-district. The data analysis technique used in this study is qualitative data analysis.